A note on the phonetic evolution of Yod-Pa-Red in Central Tibet - Hill, Nathan W. (2024)
Despite the current inconsistent spellings such as yod-red (Tournadre 1996: 229- 231 et passim, 2003), yog-red (Denwood 1999: 158 et passim), and yoḥo-red (Hu et al. 1989: 64 et passim) of the existential copula and auxiliary verb which is pronounced as yɔɔ̀ reè (Chang and Shefts 1964: 15) or yo:re' (Tournadre 1996: 229-231) there is widespread agreement that yod-pa-red is the etymological origin of this morpheme (Chang and Chang 1968: 106ff, Tournadre 1996: 229). It is regularly spelled yod-pa-red in the newspaper articles collected from the Mi dmaṅs brñan par (人民畫報 Peoples Pictorial).